Synthesis, characterization and electrical property of MWCNT-ZnS nanocomposite embedded in polyaniline. (12th June 2017) - Goswami, M; Mukherjee, A; Das, A K; Ghosh, R; Meikap, A K
Abstract: PANI/MWCNT-ZnS nanocomposites with different contents of ZnS wt.% have been synthesized by the chemical oxidative in situ polymerization reaction of aniline in the presence of multi-walled carbon nanotube (MWCNT). TEM, XRD, RAMAN and TGA studies have been done for the structural and thermal characterizations of the samples. The particle sizes of ZnS nanoparticles have the values in the range from 3.21 to 5.08 nm. XRD spectrum reveals the co-existence of MWCNT, ZnS in PANI matrix, where ZnS forms a hexagonal structure. TGA result shows that nanocomposite becomes more thermally stable with increase in ZnS content. The dc electrical transport property of PANI/MWCNT-ZnS nanocomposites has been investigated within a temperature range 77 K  ⩽   T   ⩽  300 K. The dc conductivity follows a 3D variable range hopping (VRH) model. A large magnetoconductivity change (23.1%) is observed for 2 wt.% ZnS content in PANI/MWCNT-ZnS, which is explained by the wave function shrinkage model.